Prevalência e fatores de risco de anticorpos anti-Neospora caninum em cães do município de Poconé, Mato Grosso - Grangeiro, Juliana Maria Vasconcelos (2013)
The present study evaluated the prevalence of anti-Neospora caninum antibodies in dogs from Poconé municipality, State of Mato Grosso and associate to possible risk factors to infection. Serum samples of 320 dogs from urban and rural areas were evaluated by means the immunofluorescence antibody test (IFAT) with cutoff of 1:50. The variables sex, age, contact with livestock and wild animals, diet, environment and access to streets were evaluated by the Chi-Square or exactly Fischer test when necessary. Of the analyzed samples 69 dogs (21.5%; 95%IC: 17.3-26.6%) were seropositive and presented the titers: six dogs with titers of 50 (8.7%), 13 with titers of 100 (18.8%), 12 with titers of 200 (17.3%), 11 with titers of 400 (16.0%), 11 with titers of 800 (15.9%), nine with titers of 1600 (13.0%) and seven with titers of 3200 (10.0%). It was not observed significant association between urban 19.4% (31/160; 95%IC: 13.6-26.4%) and rural (38/160; 95%IC: 17.4-31.2%) (P>0.05). Among studied variables only the dog´s hunting habit and grazing was associated with N. caninum seropositivity (P<0.05). Our results demonstrate that N. caninum are present in Poconé, MT and the contact of dogs and wild animals are associate with antibodies anti-N. caninum in dogs.